EVALUATION OF THE IMPLEMENTATION OF OCCUPATIONAL SAFETY AND HEALTH IN LEARNING LIGHT VEHICLE ENGINE MAINTENANCE - Pirhan Anugerah; Nurcholish Arifin Handoyono; Sigit Purnomo (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2025)
This study aims to evaluate the implementation of Occupational Safety and Health (OSH) in the Light Vehicle Engine Maintenance subject at SMK Cokroaminoto Pandak Bantul. The evaluation model used is the CIPP model (Context, Input, Process, Product). This research employs a qualitative approach with data collection techniques including interviews, observations, and documentation. The results of the study show that: (1) OSH has become an important part of the school's vision and mission and is aligned with industry standards; (2) teachers already have an understanding and guidelines for OSH, although facilities and infrastructure are still limited; (3) obstacles in OSH implementation include students' lack of understanding and discipline, as well as suboptimal supervision; and (4) the implementation of OSH has had a positive impact on increasing students' awareness, especially during fieldwork practice.